Use of English on General Service and Niaga Service Information in Namlea Buru District and its Implications in Indonesian Teaching - Musyawir Musyawir (Universitas Muhammadiyah Mataram, 2020)
This study aims to describe the forms of error / inaccuracy in the use of Indonesian in public services and commercial services in Namlea, Buru Regency, to describe what factors cause Indonesian language misuse in public services and commercial services in Namlea, Buru Regency, and to describe the implications of the use of Indonesian in public services and commercial services in Namlea, Buru Regency in teaching Indonesian. The results of this study indicate that 1. The forms of errors found in public service information in Namlea, Buru Regency, include (1) spelling errors, namely errors in writing words, errors in using punctuation, and errors in using capital, (2) errors in diction. 2. The forms of errors found in trade service information in Namlea Buru district, include (1) spelling errors, (2) diction errors, (3) word structure errors, and (4) errors due to the use of foreign terms. 3. Factors causing the errors contained in information on public services and commercial services in Namlea, Buru Regency can be described as follows. (a) Factors that cause spelling errors, (b) Factors that cause diction errors, c. Factors that cause errors in word structure, (d) Factors that cause errors due to the use of foreign terms, Furthermore, the implications of using Indonesian in information.